2018
DOI: 10.1186/s12882-018-0941-2
|View full text |Cite
|
Sign up to set email alerts
|

Once-weekly hemodialysis combined with low-protein and low-salt dietary treatment as a favorable therapeutic modality for selected patients with end-stage renal failure: a prospective observational study in Japanese patients

Abstract: BackgroundFor patients with end-stage renal failure (ESFR), thrice-weekly hemodialysis is a standard care. Once-weekly hemodialysis combined with low-protein and low-salt dietary treatment (OWHD-DT) have been rarely studied. Therefore, here, we describe our experience on OWHD-DT, and assess its long-term effectiveness.MethodsWe instituted OWHD-DT therapy in 112 highly motivated patients with creatinine clearance below 5.0 mL/min. They received once-weekly hemodialysis on a diet of 0.6 g/kg/day of protein adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…Furthermore, the patients enrolled in this program experienced slower declines in RKF, better control of anemia and mineral disorders, and lower hospitalization rates while maintaining a good nutritional status when compared to those who initiated conventional thrice-weekly hemodialysis. Consistent findings were observed in a prospective cohort from Japan [92]. …”
Section: How To Protect Rkfsupporting
confidence: 71%
“…Furthermore, the patients enrolled in this program experienced slower declines in RKF, better control of anemia and mineral disorders, and lower hospitalization rates while maintaining a good nutritional status when compared to those who initiated conventional thrice-weekly hemodialysis. Consistent findings were observed in a prospective cohort from Japan [92]. …”
Section: How To Protect Rkfsupporting
confidence: 71%
“…Moreover, the present study showed that patients with 2 times of hemodialysis per week were more likely to have lower HRQOL in Burden of Kidney disease. It is in the same line that 3 times weekly hemodialysis has been standard way of treatment to control uremia [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Incremental dialysis is of particular interest; the concept, which originated from PD, supports implementing a progressively higher dialysis dose with a progressively reduced residual kidney function [129][130][131][132][133][134][135]. Several schedules are available, whose is beyond the aim of this paper.…”
Section: Choice Of Renal Replacement Therapy Has An Ecologic Impactmentioning
confidence: 99%
“…Several schedules are available, whose is beyond the aim of this paper. In any case these patient-friendly approaches seem to allow preserving kidney function and lowering dialysis related comorbidity, in particular in association with dietary management [129][130][131][132][133][134][135]. From an ecologic point of view, incremental dialysis allows us to limit the carbon footprint, wastes and social costs, although, almost paradoxically, the treatment costs borne by the institutions providing care may be higher [136].…”
Section: Choice Of Renal Replacement Therapy Has An Ecologic Impactmentioning
confidence: 99%